Analysis of epithelial-mesenchymal transition markers in the histogenesis of hepatic progenitor cell in HBV-related liver diseases. Issue 1 (December 2016) - Xu, Wei; Wang, Nong-Rong; Wang, Hua-Feng; Feng, Qiong; Deng, Jun; Gong, Zhi-Qiang; Sun, Jian; Lou, Xiao-Liang; Yu, Xue-Feng; Zhou, Lv; Hu, Jin-Ping; Huang, Xiao-Feng; et al.
Abstract Background The origin and heterogeneity of hepatic progenitor cells (HPCs) remain unclear. This study aimed to investigate the involvement of epithelial-mesenchymal transition (EMT) in the histogenesis of HPCs. Methods Surgical liver specimens from patients with HBV-related hepatitis and cirrhosis were investigated with double immunofluorescence labeling to detect antigens associated with HPCs and EMT. Ductular reactions were subjected to quantitative reverse transcription PCR following isolation by laser capture microdissection. Electron microscopic examination was performed to find an ultrastructural evidence of EMT. Results The number of EpCAM-positive HPCs was proportional to the disease severity. The S100A4 expression of HPCs was firstly observed in mild hepatitis and increased significantly in moderate hepatitis, but decreased in severe hepatitis and cirrhosis. The levels of MMP-2, Twist, and Snail increased in direct proportion to the number of HPCs. Some hepatocytes adjacent to portal tracts in cirrhosis showed positivity for MMP-2. Although CK7 and E-cadherin levels decreased in mild and moderate hepatitis, HPCs re-expressed both of them in severe hepatitis and cirrhosis. However, HPCs expressed neither vimentin nor αSMA. The relative mRNA expression levels of EpCAM and EMT-associated markers supported immunohistochemical results. Electron microscopic examination demonstrated the existence of intercellular junctions among HPCs, cholangiocytes, and intermediate hepatocyte-like cells. Conclusion We provided preliminary evidence for the involvement of EMT in the histogenesis of HPCs from cholangiocytes in HBV-related liver diseases. HPCs may re-transdifferentiate into hepatocytes, and the differentiation direction depends, at least in part, on interactions between HPCs and the surrounding microenvironment, especially the non-resolving inflammation caused by HBV infection.